Sociology beyond societies : mobilities for the twenty-first century - Urry, John. (London ; New York : Routledge, 2000)
Publisher description: John Urry argues that, if sociology is to make a pertinent contribution to the global era, it must abandon its original aim--the study of society as a set of institutions--and switch focus instead to the study of both physical and virtual movement. In considering this "sociology of mobilities" the book concerns itself with the travel of people, ideas, images, objects, messages, waste products and money across international borders, and the implications these mobilities have for the experiences of time, space, dwelling and citizenship. Sociology beyond societies extends recent debate about globalisation both by providing an analysis of how mobilities reconstitute social life in uneven and complex ways, and by arguing for the significance of objects, senses, time and space in the theorising of global processes.
1. Societies -- 2. Metaphors -- 3. Travellings -- 4. Senses -- 5. Times -- 6. Dwellings -- 7. Citizenships -- 8. Sociologies.
Includes bibliographical references (pages 212-231) and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Sociology -- Philosophy; SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Anthropology -- General; Sociology -- Philosophy; Sociologie; Electronic books